The effect of aminophylline on trans-diaphragmatic pressure in isoflurane anaesthetised dogs undergoing castration - PAVLIDOU, K.; SAVVAS, I.; MOENS, Y.; KAZAKOS, G.; RAPTOPOULOS, D. (Journal of the Hellenic Veterinary Medical Society, 2018)
The trans-diaphragmatic pressure (Pdi)is the main indicator of diaphragmatic contractility and the influence of many different drugs on Pdi has already been studied. The main aim of this study was to investigate the effect of aminophylline on Pdi in anaesthetised dogs. Eighteen, healthy, client-owned, male dogs undergoing castration were recruited in the study. All the animals were premedicated with dexmedetomidine and morphine. Anesthesia was induced with propofol to effect and maintained with isoflurane in oxygen. Animals were randomly allocated into two groups. In the animals of the aminophylline group (group A), aminophylline was administered as an intravenous bolus at 4mg/kg after induction, whereas in the animals of the control group (group C), no aminophylline was given. When the surgical plane of anesthesia was achieved, two balloon catheters, one in the stomach and one in the mid-third of the oesophagus were inserted for Pdi measurement. The two groups differed non-significantly with regards to Pdi (p=0.182). The results of the study could be viewed as an indication that the aminophylline might increase diaphragmatic contractility if also proven in a larger population of animals’.